Various Types of Biodiesel as Sustainable Fuel Choices: a Review - Maksum, Hasan; Ilham, Ilham; Purwanto, Wawan (Universitas Negeri Padang, 2023)
The energy sources used today are non-renewable energy. Non-renewable energy, if used continuously will experience scarcity. Therefore, renewable energy sources are needed as an alternative energy. One of alternative energy source is biodiesel. Biodiesel is an alternative fuel produced from vegetable or animal raw materials. The sustainability and diversity of biodiesel feedstock sources make it an attractive option for reducing dependence on fossil fuels. The problem is that all existing natural resources have not been utilized, the potential availability of raw materials and their production, lack of knowledge about the types of biodiesel and other types of biodiesel that can be developed. This article aims to review the different types of biodiesel that are being researched and developed and increasing knowledge and becoming a reference regarding the potential of natural resources and the opportunity to develop other types based on the potential of available natural resources. The research method used is a literature review study using the Publish or Perish 8 application, on the search menu Google Scholar is selected. Article search retrieved September 19, 2023. Based on this search, 14 articles were obtained that were in accordance with this research. The research results showed that the various types of biodiesel are bintaro oil, hazelnut oil, corn oil, crude palm oil, hydrotreated vegetable oil, kapok seed oil, rubber seed oil, used cooking oil, kesambi oil and graphene nanoplatelets. Each type of biodiesel has its own advantages, while the biodiesel feedstock that has the potential to be produced in large quantities is palm oil. This research also suggests that Indonesia's natural resource potential is very large, so we can also process and develop other types of biodiesel which can be used as alternative fuel.